Vascular Risk Factor and Cognitive Impairment in Elderly - Rohmania Setiarini; Made Rika Anastasia Pratiwi; Mirzaulin Leonaviri (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
The elderly are more likely to experience cognitive impairment, especially those who have a vascular risk factor. The purpose of this study was to determine the relationship between vascular risk factor and cognitive impairment in the elderly. Observational research method with cross-sectional design consist of 79 participant in Tresna Werdha Puspa Karma Social Institution, Mataram from October to November 2021. The subjects were measured blood pressure, weight and height to obtain BMI, glucose level, and total cholesterol. Furthermore, each participant underwent a cognitive function test using Moca-INA. Data were analyzed by chi-square and logistic regression. Diabetes mellitus (p =0.09), hypertension (p =0.037), lower education (p =0,01) and hight blood pressure (p =0.036) were associated with poor cognitive function.